Mobilidade produtiva e crescimento da produtividade no agronegócio brasileiro - Pedro Meiners; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– To better comprehend the growth trajectory of Brazilian agriculture, it is necessary to understand the productivity movement of different classes of producers within the country, that is, to verify whether poorer producers are converging in productivity with larger ones. Stochastic frontier analysis is used to compare total factor productivity (TFP) gains of three different strata of agricultural producers in Brazil. Using data from the agricultural censuses of 2006 and 2017 at the micro-regional level, we estimate both technological progress (TP) and technical efficiency change (TEC) of Brazilian agriculture for different farm sizes. Our results suggest that technological advancements are reaching all farm sizes, but they are concentrated in the larger producers, which contributes to a divergence in productivity within Brazil. Furthermore, the increase in inefficiency indicates that all farm sizes lack the conditions to quickly absorb the technological progress.
Keywords: Q1; C23; D24; 330; agriculture; productivity; technical progress; stochastic frontier